Applied calculus : for management, life, and social sciences - Harshbarger, Ronald J.; Reynolds, James J. (Massachusetts : D.C. Health and Company, 1989)
The purpose of this text, then, is to present mathematical skills and concepts and to apply them to areas that are important to students in the management.
Chapter 0. Algebra concepts -- Chapter 1. Functions -- 2. Derivatives -- 3. Applications of derivatives -- 4. Exponential and logarithmic functions -- 5. Indefinite integrals -- 6. Definite integrals -- 7. Functions of two or more variables.
Includes index.
Keywords: LIFE SCIENCES -- MATHEMATICAL MODELS